Audiovisual project «Zvukoizolyatsia»: specifics of conceptual and spatial implementation of the compositional and technical principles - Prykhodko, Anna (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2024)
The relevance of the study is determined by the insufficient development of the stated problems, the lack of a systematic analysis of projects of electroacoustic and audiovisual synthesis in academic music. The introduction of technical materials from the private archives of the project authors into scientific circulation also seems important. Usually, such «internal» documents do not come to the attention of researchers due to their utilitarian nature in the organizational process of the implementation of a work/project, but sometimes they can open perspectives for the further study of similar artistic phenomena. Most often, large-scale projects, in particular audiovisual ones (requiring the involvement of significant resources to ensure technical organization), are performed «one time only»; mentions of them gradually disappear from the information space. The analysis of the peculiarities of the implementation of audiovisual projects contributes to the systematization and differentiation of existing and new perspectives of the study of this synthetic phenomenon in the modern art history discourse. The main objectives of the study are to reveal the specifics of the implementation of spatial compositional and technical principles and the peculiarities of the implementation of one of the landmark experiments in the field of electroacoustic and audiovisual synthesis, «ZvukoIzolyatsia» project (2011/2012), to understand its significance in the modern artistic space, to outline the particular features of reception of musical-spatial performance. The research methodology: historical and functional method to define and forecast the place and role of the project in the modern art space; analytical method to reveal the specifics of the embodiment of spatial compositional and technical principles; intent analysis to find the author's intentions; the method of theoretical generalization to summarize the results of the research. Results and conclusions. The first and second «ZvukoIzolyatsia» became one of the most daring and vivid experiments in the field of electroacoustic and visual synthesis. In the aesthetic search for musical expressiveness, in the logical regularity of the development of the art of the 21st century, the project covered the most important innovations of the compositional technique of the last century (in particular, the achievements of the electroacoustic avant-garde, the use of real-time sound processing technologies, the application of sonoristic principles that become a category of musical thinking, manipulation of objects which can make sounds, etc.). The expansion of the boundaries of the academic environment or a complete departure from it (in the 2012 project), as a desire to overcome the space of the concert hall, and the involvement of industrial spaces — conventionally marginal — forms a new type of aesthetic disposition (P. Bourdieu). The dialogue with the space is carried out as an action (artistic gesture) aimed at expanding the perception models of artistic expression, thanks to which the horizon of listening expectations is expanded. This leads to the formation of a new aesthetic experience in the recipient, which will potentially influence the reception of other works of modern academic practice. The involvement of VJ technologies creates a new communication situation, creating a fundamentally new conceptual field, which in some cases can act as a mechanism for destroying stereotypes of artistic thinking. Audiovisual synthesis in relation to musical art creates new perspectives for multifaceted work with audio and visual material. Researching the experience of using audio and video technologies, their interaction with the spatial factor contributes to the development of electroacoustic music. The proposed investigation can to some extent serve as a methodological aid in further art studies of audiovisual compositional projects.